Pengaruh Sales Growth, Firm Size, Debt Policy, Return On Asset terhadap Nilai Perusahaan pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia - Lusiana Veronika Sinaga; Antonia Masriani Nababan; Annisa Nauli Sinaga; Thomas Firdaus Hutahean; Siti Tiffany Guci (COSTING : Journal of Economic, Business and Accounting, 2019)
The company was builded to maximixing the wealth of their owner or their stokeholders. The company’s goal can be achieved by maximizing the firm value.The purpose of this research is to find out the impact of some variables such as Growth of Sales, Firm Size, Debt Policy, and ROA, to Firm Value on companies to Property and Real Estate period 2013-2016.Purposive sampling method was used in sampling and 26 companies were used as sample.Method of observation and using Linear Regression Analysis as the Analysis technique and 26 companies were used as sample.The result showed that Growth of Sales has significant and not impact on Firm Value, Firm Size has a positive and significant impact on Firm Value, Debt Policy not impact and not significanton firm value. And ROA has a positive and significant impact to Firm Value.The firm value is very important because the higher is the firm value, the higher is the wealth of the company’s owner. To the investors that they may point out the Return on Asset and before make an investment. Keywords : Sales Growth, Firm Size, Debt Policy, Return on Asset